2022
DOI: 10.3390/jcm11112999
|View full text |Cite
|
Sign up to set email alerts
|

Health Perception among Female COVID-19 Patients. Comment on Fernández-de-las-Peñas et al. Female Sex Is a Risk Factor Associated with Long-Term Post-COVID Related-Symptoms but Not with COVID-19 Symptoms: The LONG-COVID-EXP-CM Multicenter Study. J. Clin. Med. 2022, 11, 413

Abstract: We read with interest the original paper by Fernández-de-las-Peñas et al. [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…Previous studies have shown a higher risk of developing LC with increasing age, female sex, symptom burden, hospitalization during acute COVID-19, presence of comorbidities, smoking, obesity, socioeconomic deprivation, and belonging to an ethnic minority (Carvalho-Schneider et al, 2021; Emecen et al, 2023; Jacobs et al, 2020; Subramanian et al, 2022; Sudre et al, 2021). In addition, a study has indicated that the female sex is a worse predictor of LC, even if the disease is less severe during that phase (García et al, 2022). A prospective cohort study from Iran has shown a significant association between LC and some factors, including age, underlying diseases, acute phase symptoms, weight loss, and history of skin sequel in the acute phase (Larijani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown a higher risk of developing LC with increasing age, female sex, symptom burden, hospitalization during acute COVID-19, presence of comorbidities, smoking, obesity, socioeconomic deprivation, and belonging to an ethnic minority (Carvalho-Schneider et al, 2021; Emecen et al, 2023; Jacobs et al, 2020; Subramanian et al, 2022; Sudre et al, 2021). In addition, a study has indicated that the female sex is a worse predictor of LC, even if the disease is less severe during that phase (García et al, 2022). A prospective cohort study from Iran has shown a significant association between LC and some factors, including age, underlying diseases, acute phase symptoms, weight loss, and history of skin sequel in the acute phase (Larijani et al, 2022).…”
Section: Introductionmentioning
confidence: 99%